Relationship of Diet and Sports Habits with Blood Pressure Hypertension Patients in Nanggalo Padang Community Health Center Year 2018 - ., Herwati; Sartika, Wiwi (KnE Life Sciences, 2019)
Background: Hypertension as the silent killer causes premature death, predicted by 2025 to about 29% of hypertensive adults. Riskesdas 2013, 25.8% of Indonesia’s population had hypertension. The prevalence of hypertension in West Sumatra in 2017 included three diseases, measurement of population blood pressure ≥ 18 years by sex in 2017 hypertensive sufferers 23.0%. Hypertension that is not within normal limits leads to complications, resulting in extensive organ damage, rupture of blood vessels to the brain, to Heart, decreased consciousness, coma, or stroke. Prevention and control hypertension with medication adherence and adherence to diet hypertension, a healthy diet with Dietary Approach to Stop Hypertension (DASH) and regular exercise. The purpose of this research is to know the relationship between diet and exercise habits a blood pressure of hypertension sufferers at Nanggalo Padang Community Health Center Year 2018. Subjects and Method: Analytical descriptive research type, cross-sectional design. The population of the study was all hypertensive patients who came to the Nanggalo Padang Community Health Center in the year 2018. The sample size was 38. Data were collected using questionnaires. Accidental sampling technique. Univariate data analysis is presented with a frequency distribution table and bivariate analysis using Chi-Square statistical test; 95% confidence degree with α = 0,05 if p ≤ α (0,05). Result: Of research (57,9%) diet less good. (52.6%) bad exercise habits, (60,5%) is not within normal blood pressure. There is a significant relationship between a diet a normal blood pressure of hypertension patients and there is a significant relationship between exercise habit a normal blood pressure of hypertension patients at Nanggalo Padang Community Health center Year 2018. Conclusion: Health officers are advised to provide counseling, displaying posters and exercise patterns of hypertension patients waiting room.